Genotypic characterization of Porphyromonas gingivalis isolated from subgingival plaque and blood sample in positive bacteremia subjects with periodontitis (2008)
The objective of this study was to investigate clonal relationship among Porphyromonas gingivalis isolated from subgingival plaque and blood samples in positive transient bacteremia subjects with periodontitis. Unrelated patients with general chronic periodontitis or general aggressive periodontitis requiring scaling and root planing (SRP) were included in the study. Genotyping of each isolate was performed using pulsed field gel electrophoresis technique. Genetic relatedness of strains isolated within an individual or between different patients was determined by dendogram analysis. Following SRP, from 16 patients, seven patients showed positive P. gingivalis bacteremia and nine were negative. Thirty‐two strains were isolated from subgingival plaque and blood samples before and during induced transient bacteremia. The majority of the patients harboured one clonal type. Two patients showed different clones in plaque and blood samples suggesting that more than one clone can be found in subgingival plaque. P. gingivalis isolates from periodontitis patients after transient bacteremia following SRP, revealed a high heterogeneity among isolates. In 6/16 subjects the same P. gingivalis isolate was found in the blood and in oral cavity. P. gingivalis heterogeneity suggests no association of a unique clonal type with transient bacteremia.